Новый подвид ящерицы куринской Lacerta portschinskii nigrita ssp. n. из Восточного Закавказья - Бакрадзе, М.А. (Вестник зоологии, 1976)
The new subspecies is found in the mauntain regions of south-eastern Georgia and northern Armenia. It differs from the nominative form by a much darker colour of the body upper side and by certain peculiarities of the squamous cover.